The integration of fingerprint authentication with punch card system / Azliana Ghazali - Ghazali, Azliana (2004)
This project is a descriptive study on the integration of biometric technology that focuses on the fingerprint authentication with the punch card system. A study was carried-out to determine the authenticated user identification using the biometric technology to clock in/out employees working hours in the organization. According to the research, Biometric-Time Clock is the most prominent biometrics technology, which is low cost and easy of integration of fingerprint authentication device with the time and attendance management system. The strength is in its acceptance, convenience and reliability. It is suitable to use for the FTMSK as the enhancement to the manual punch card system.